La potenciaen la precisión demiembros inferiores de los futbolistas de la categoría sub 10 de la escuela permanente de fútbol dioses de fútbol período septiembre 2016 – diciembre 2016. - Carguaytongo Silva, Bryan Andrés (2017)
This research is about the power in the lower members' precision in the children's categories, so it was taken the population of the Permanent School of football Gods of soccer of the Riobamba city, the sample in the category sub 10, was formed by 18 athletes between 9 and 10 years of age. The present investigation is under an approach or paradigm critical propositive, the level is exploratory and the type of research is field and bibliographical. Within the analysis of this work, two tests were used, for the Bosco test power and for the accuracy of the pass precision test, which were applied to the 18 athletes, both before and after the exercise program of the power and The precision. After having taken the corresponding pre-test, the 5-week power and precision exercise program was executed with 3 sessions for each of 80 minutes, whereby the proposal seeks the necessary importance to the precision work and the power of The lower limbs in the infant categories, a basis of a series of specific exercises and functional looking for the improvement of them. Exercises and the activity are done directly with the perfection of ball balloon accuracy, mainly with the inner edge, and power in the lower limbs. At the end of the exercise program, the post-tests were executed, both the pass-accuracy test and the Bosco test. For the statistical data processing it was used the analysis in the statistical test Students for the test of samples related to the paired. After having analyzed and interpreted the results, it was concluded that the intervention performed improved the power in the lower limbs precision to reach a p <0.001 in each of the analyzed variables such as power (flight time, speed Of takeoff and height) and the precision of the inferior members.